Latissimus Dorsi Tendon Transfer with GraftJacket® Augmentation to Increase Tendon Length for an Irreparable Rotator Cuff Tear - John G. Skedros; Tanner R. Henrie (Case Reports in Orthopedics)
Massive irreparable rotator cuff tears can be reconstructed with latissimus dorsi tendon transfers (LDTT). Although uncommon, the natural length of the latissimus dorsi tendon (LDT) could be insufficient for transfer even after adequate soft tissue releases. Descriptions of cases where grafts were needed to lengthen the LDT are therefore rare. We located only two reports of the use of an acellular dermal matrix to increase effective tendon length in tendon transfers about the shoulder: (1) GraftJacket patch for a pectoralis major tendon reconstruction and (2) ArthroFlex® patch for LDTT. Both of these brands of allograft patches are obtained from human cadavers. These products are usually used to cover soft tissue repairs and offer supplemental support rather than for increasing tendon length. Extending the LDTT with GraftJacket to achieve adequate length, to our knowledge, has not been reported in the literature. We report the case of a 50-year-old male who had a massive, irreparable left shoulder rotator cuff tear that was reconstructed with a LDTT. The natural length of his LDT was insufficient for transfer. This unexpected situation was rectified by sewing two patches of GraftJacket to the LDT. The patient had greatly improved shoulder function at two-year follow-up.